Potential risks of COVID-19 among healthcare workers - Shakya, Nona; Gaire, Bipula; Khadka, Shanti; Nepal, Manju (Journal of Chitwan Medical College, 2021)
Background: Healthcare workers have a potential risk of COVID-19 as they are at the front line of the COVID-19 outbreak response. This study aimed to assess the potential risk of COVID-19 infection among healthcare workers at COVID -19 treatment center. Methods: A hospital based cross-sectional study design was undertaken to conduct this study. A snowball networking sampling method was used to select the participants. Total 387 health care workers participated in the study from July 18, 2020 to September 22, 2020. The WHO COVID-19 risk assessment tool was used to collect data from study participants. Descriptive statistics and inferential statistics binary logistic regression were done through SPSS 16 version. Results: There was a high level of occupational exposure (88.9%) to the COVID-19 virus and a higher potential risk of COVID-19 infection (75%) among exposed healthcare workers. Among those who had occupational exposure 7% and 21 % did not use personal protective equipment during healthcare interaction and performing aerosol generating procedures respectively. Male healthcare workers, registered nurses, medical doctors, and auxiliary nurse midwives were found the potential risk of COVID-19 infection. Healthcare workers with less supply of PPE had three times higher potential risk of COVID-19 infection. Conclusions: Healthcare workers had a higher occupational exposure and higher potential risk of COVID 19 infection. Healthcare workers had poor adherence to infection prevention and control measures. Healthcare workers should ensure proper use of personal protective equipment and adherence to infection control measures and adequate supply of PPE must be there to protect the healthcare workers from COVID-19 infection.